Estudo de sintomas de despersonalização em pacientes com migrânea e controles - Ana Carolina Sarquis Salgado (2015)
Introduction: Depersonalization, a feeling of strangeness towards the self, is an intriguing phenomenon, and, up until now, it was subjected to few investigations. Symptoms of depersonalization - including derealization, deaffectualization and anomalous subjective recall may manifest as transient episodes, along the course of neuropsychiatric disorders or occur as a primary disease, namely depersonalization and derealization disorder. Migraine is a recurrent primary headache found in 15,8% of the Brazilian population, and around 30% of patients with migraine report premonitory aura. Over the last years, studies have investigated the relationship between migraine and depersonalization and hypothesized a common pathophysiological mechanism. It is relevant to note that both migraine and depersonalization disorder present a high rate of comorbid psychiatric disorders, specially anxiety and depression. Objectives: The goals of this study are to evaluate the frequency and duration of depersonalization symptoms in patients suffering from migraine with and without aura and healthy controls, controlling for the co-ocurrence of depression and anxiety, and perform the translation and cultural adaptation of the Cambridge Depersonalization Scale. Methods: An observational transversal study was conducted, using structured psychiatric interviews in 49 patients with migraine according to the criteria of the International Headache Society (2013) and 30 healthy controls. To diagnose axis I psychiatric disorders, MINI structured interviews were performed. The Cambridge Depersonalization Scale (Brazilian Portuguese version) and clinical interviews were used to identify depersonalization symptoms, BDI and BAI to quantify depressive and anxious symptoms respectively and MIDAS to evaluate migraine impact in the patients work and daily activities. The impact of aura in depersonalization symptoms has also been evaluated. Results: Transient depersonalization experiencies within the past six months were found in 59,1% of the migraine group and 43,3% of the controls. Clinically significant depersonalization, identified by a semi-structured clinical interview, was diagnosed in 7,5% of the sample, and associated to the diagnosis of depressive or anxious disorders in 85% of the cases. Depersonalization and derealization disorder was diagnosed in only one case, which represents 1,3% of the total sample and 2,1% of the migraine group. An association between the occurrence of aura and the frequency or intensity of depersonalization experiences has not been found. Conclusion: In the migraine group, clinically significant depersonalization experiencies are strongly related to depression and anxiety, therefore, it is not possible to assume an independent relation.